2020
DOI: 10.1186/s12870-020-02602-1
|View full text |Cite
|
Sign up to set email alerts
|

A member of wheat class III peroxidase gene family, TaPRX-2A, enhanced the tolerance of salt stress

Abstract: Background: Salt and drought are the main abiotic stresses that restrict the yield of crops. Peroxidases (PRXs) are involved in various abiotic stress responses. Furthermore, only few wheat PRXs have been characterized in the mechanism of the abiotic stress response. Results: In this study, a novel wheat peroxidase (PRX) gene named TaPRX-2A, a member of wheat class III PRX gene family, was cloned and its response to salt stress was characterized. Based on the identification and evolutionary analysis of class I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 85 publications
2
44
0
Order By: Relevance
“…Some genetic evidences suggested that class III peroxidase is an abiotic stress-responsive enzyme in different plant species. For example, the overexpression of AtPrx64 could enhance the tolerance of tobacco to aluminum stress ( Wu et al, 2017 ), and the overexpression of TaPRX-2A in wheat exhibited an enhanced tolerance to salt stress ( Su et al, 2020 ). Similarly, the overexpression of CrPRX, a Catharanthus roseus peroxidase, improved tolerance of tobacco to salt and drought stress ( Jaggi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some genetic evidences suggested that class III peroxidase is an abiotic stress-responsive enzyme in different plant species. For example, the overexpression of AtPrx64 could enhance the tolerance of tobacco to aluminum stress ( Wu et al, 2017 ), and the overexpression of TaPRX-2A in wheat exhibited an enhanced tolerance to salt stress ( Su et al, 2020 ). Similarly, the overexpression of CrPRX, a Catharanthus roseus peroxidase, improved tolerance of tobacco to salt and drought stress ( Jaggi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant defence system can alleviate oxidative damage in response to salinity/oxidative stress [1,4,21]. Our physiological work showed that the antioxidative enzymes, POD (Fig.…”
Section: Potential Deus May Determine Differences Between Shanghaijimmentioning
confidence: 81%
“…In addition, salinity stress tolerance mechanisms also include a series of ROS scavenging enzyme genes [4], compatible solute synthesis genes [4,19,20] and ion transporters [1,4], which enhance plant adaptations to salinity stress. Some studies have shown that overexpression of the stress-associated genes encoding the ROS scavenging protein TaPRX-2A [21], compatible solute KvP5CS1 [22], ion transporter AtNHX1 [23] and SpSOS1/NHX7 [10] results in enhanced tolerance to salinity stress in transgenic plants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This bryophyte is thus a useful tool to study responses to abiotic stress. Peroxidases are enzymes known to change their expression pattern in response to different types of stress [ 16 , 17 ]. Here, we selected different abiotic stresses and monitored in a time course both peroxidase activity and isoform pattern from protein extracts of P. patens gametophores grown in liquid medium.…”
Section: Resultsmentioning
confidence: 99%